الاستقرار السياسي للوطن في ضوء الحديث النبوي - Mahmud Abdullah (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2024)
Islamic law preceded all systems and constitutions that were concerned with the concept of political stability and how to achieve it on the ground through the texts of the Holy Qur'an, the Sunnah of the Prophet and the legal rules that scholars deduced from the texts, which ensure happiness for human beings and spread security and tranquility in the hearts of people. Maintaining political stability is one of the most fundamental goals of Islamic legislation. The texts of the Qur'an and the Sunnah of the Prophet came with rules that ensure the maintenance of stability in general and political stability in particular.And political stability after a relative phenomenon in meaning and application, there is no country that enjoys complete stability, there are varying degrees of stability according to the process of interaction between demands and support on the one hand and response to the system on the other. The concept of political stability is one of the most complex and ambiguous concepts, and it is a relatively standard concept that varies from one country to another, according to the different definitions of the concept of political stability among the infidels and politicians. Political stability is not a stage that society reaches, as the general goal of the various political systems is to achieve more achievement and progress, as well as it is a goal, not a reality, not just a description of a typical situation, but fluctuates according to the conditions that help to achieve it. Political stability has elements that have made it an integrated intellectual and structural structure that distinguishes it from other systems and philosophies, as it is dominated by the intentional value character in accordance with the provisions and legislation stated in the Holy Qur'an and the Sunnah of the Prophet. Among the elements of political stability is the supremacy of Sharia and the authority of the nation, the integration between the government and the people, the obligation to obey the first known thing, the balance between the system and members of society in rights and duties, and the unity of the nation as rulers and ruled, and by achieving these components, political stability occurs and thus society enjoys prosperity and well-being and security prevails in society. The goal of political stability is: preserving religion, establishing the world over religion, achieving security, achieving social justice, and the goodness of the world and the prosperity of the hereafter.